13=x-49

Simple and best practice solution for 13=x-49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13=x-49 equation:



13=x-49
We move all terms to the left:
13-(x-49)=0
We get rid of parentheses
-x+49+13=0
We add all the numbers together, and all the variables
-1x+62=0
We move all terms containing x to the left, all other terms to the right
-x=-62
x=-62/-1
x=+62

See similar equations:

| 2m=-6(2)+-2 | | p/2+1=-4 | | 17+4c=13 | | 17=6m-7 | | 24a+10=180 | | –3=7−2b | | 1=5+–2j | | 5(x+1)×7(x+3)=146 | | 5-x=15/5 | | 13=3−2y | | 15.5+d=56.03 | | 525000+13x=100000+16x | | 14x—10x—3x=7 | | 9−2c=–11 | | (34x+4)=196 | | 6x*3=11 | | n/3+1=-3 | | t−8=1 | | x+(3x)+(2x-20)=340 | | 9999(9x+9999999)^2=9999999 | | −6+5(−y−3)=(−8y+9)−1 | | Z^2+1z-30=0 | | -15-5q=-6q | | -6x-7=3x-8 | | -10+20h=19h | | 4b+2=-9 | | 0.4x−0.7=6.5 | | 5x-15=7x-28 | | 6+3t=5t+20 | | 1/2x−7=20 | | -10-9y=8+9y | | 1/3x−2=23 |

Equations solver categories